Orofacial Granulomatosis in a Child - Reena Razdan; Maxwell D. Newby; Michele M. Carr (Case Reports in Pediatrics)
Orofacial granulomatosis (OFG) is a rare, idiopathic disorder of the orofacial region. It is clinically characterized by persistent and/or recurrent enlargement of the soft tissues of the oral and maxillofacial region, often manifesting as labial enlargement and swelling of intraoral sites such as the gingiva, tongue, and buccal mucosa. Full-thickness mucosal biopsy reveals noncaseating granulomatous inflammation, similar to Crohn’s disease and sarcoidosis. Thus, OFG must be distinguished from other chronic granulomatous disorders. We report a case of a young female patient who presented with labial and maxillary gingival enlargement without any identifiable systemic causes, with suggested involvement of environmental triggers.